Les « rituels » dans la publication de photos sur le réseau social Instagram : une étude appliquée au contexte brésilien - Élisabeth Eglem (Brésil(s), 2022)
This paper focuses on the concept of « ritual » in the context of online publication on Instagram. It aims to understand the contemporary modalities and significations of the « ritual » published through online pictures in Brazilian society infused with a latent spirituality but also influenced by a strong consumer culture. The methodology is « netnographic ». The discussion places information from the field in dialogue with theoretical elements.